Identifying Sexual Assault Mechanisms Among Diverse Women, New York State, 2016-2017 - Hequembourg, Amy L. ([Verlag nicht ermittelbar], 2021)
This study offers novel insights into mechanisms associated with sexual assault (SA) among sexual minority women (SMW). Experiences of bias and stigma contribute to lower rates of SA reporting by this population. This results in victims with unmet needs and fewer criminal prosecutions of SA perpetrators. This study used a mixed-methods approach to collect data from lesbian, bisexual, and heterosexual women to instigate changes that would improve responses from law enforcement, victim services, and anti-violence programs that serve SMW. This study comprised of three parts a: baseline survey, qualitative interview, and daily survey. Self-reported baseline questionnaires included topics like lifetime victimization (childhood sexual abuse, adult sexual aggression, and assault), discrimination, distress, mental health, alcohol use, and sexual history. The qualitative interviews focused on the most recent, and when applicable, the most salient adult sexual assault (ASA) incident. Interviews began by asking the participants to describe their ASA incidents with follow-probes asking about the victimization, perpetrator characteristics (gender and relationship to participant), and context of assault (role of alcohol or drugs and setting). Participants were also asked if they discussed the assault with anyone and their reasons for disclosure or non-disclosure. As well as short and long-term coping patterns. The daily survey asked participants about their mood, alcohol use, drinking contexts, and sexual experiences (consensual and non-consensual). This study contains demographic information such as: age, race, income, education, and BMI.